2015
DOI: 10.1007/s00408-015-9693-y
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 Protein Correlates with the Phenotype of Asthma

Abstract: PurposeYKL-40 is a chitinase-like protein found to correlate with asthma as well as numerous infectious and autoimmune diseases or cancer. The aim of the present study was to investigate the role of YKL-40 as a possible marker of asthma and its associations with factors differentiating phenotypes of asthma.MethodsThe study group comprised 167 patients, including 116 women and 51 men aged 18–88 years with chronic asthma. The control group comprised 81 healthy individuals, including 50 women and 31 men aged 19–8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…Furthermore, this study recorded a significant relationship between serum YKL40 levels and acute asthma exacerbation in children (p<0.001), this go in line with a previous report by Specjalski et al , who reported that in asthmatics, the level of serum YKL40 was significantly higher in the subgroup with poor control of symptoms and exacerbations compared with stable asthmatics 14. This also, was supported by Tang et al , in their study which showed higher serum YKL40 in patients with more severe or uncontrolled asthma 15.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, this study recorded a significant relationship between serum YKL40 levels and acute asthma exacerbation in children (p<0.001), this go in line with a previous report by Specjalski et al , who reported that in asthmatics, the level of serum YKL40 was significantly higher in the subgroup with poor control of symptoms and exacerbations compared with stable asthmatics 14. This also, was supported by Tang et al , in their study which showed higher serum YKL40 in patients with more severe or uncontrolled asthma 15.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we also observed the highest levels of YKL-40 and chitotriosidase in patients with COPD, further suggesting that the chitinases are not Th2-specific markers of airway disease. Interestingly, a weak association with increased BMI was observed, which has also been described previously (32). In contrast to our findings, initial studies in mice did suggest an involvement in Th2-type processes, as the expression of chitinase proteins (AMCase, Ym1, and Ym2) is dependent on IL-13 (3, 33, 34) and mice lacking Brp39 (YKL-40) have defective IL-13-induced inflammation (35).…”
Section: Discussionsupporting
confidence: 57%
“…High levels of YKL-40 in serum, bronchoalveolar lavage fluid, or sputum were found in various pulmonary disorders. In asthma, YKL-40 levels correlated with some clinical signs such as exacerbation, level of control, and obesity [66,67,68,69]. In chronic obstructive pulmonary disease, high levels of YKL-40 were shown to correlate with disease severity and overall survival [70,71].…”
Section: Chitinase-like Proteinsmentioning
confidence: 99%